Navigating the Digital Consumer Mind: Understanding the Psychological Aspects of E-commerce Success - Nugraha, Risman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
In the digital era, E-commerce has emerged as a prominent stage where psychology and business seamlessly integrate. This article extensively delves into the crucial role of psychology in achieving E-commerce success, with a focus on a profound understanding of the minds of digital consumers. The research aims to detail the roles of psychological aspects such as perception, motivation, and purchase decisions that influence online consumer behavior. The research method involves meticulous study design, a representative sample of digital consumers, and data collection through targeted research instruments. Data analysis is conducted to gain profound insights into the psychological factors that play a key role in E-commerce success. The research findings reveal how the design of platform interfaces, consumer motivation, and other psychological factors impact online purchase decisions. In-depth analysis is conducted on the mechanisms of product selection, the evaluation process, and the psychological impact on purchase conversions. The article also discusses psychological factors contributing to customer loyalty, including user experience and satisfaction. By understanding these psychological aspects, business practitioners can make more informed decisions and design more effective marketing strategies in the context of E-commerce. The research conclusion provides a summary of key findings, practical implications for the business world, and recommendations for further research in this field. This article offers profound insights into the marriage of psychology and business in the context of E-commerce, paving the way for further research and the development of innovative business strategies